PENGARUH KEPEMILIKAN SAHAM EKSEKUTIF, CEO EDUCATION DAN PERGANTIAN AUDITOR TERHADAP KECURANGAN LAPORAN KEUANGAN PADA PERUSAHAAN BUMN (STUDI EMPIRIS PADA PERUSAHAAN BUMN YANG TERDAFTAR DI BEI) - Irvan Sanjaya; Suyanto Suyanto; Gustin Padwa Sari (Universitas Muhammadiyah Metro, 2021)
This study aimed to examine the factors that influenced the fraudulent financial statements of state-owned companies (BUMN) on the Indonesia Stock Exchange. The factors that influenced the fraudulent financial statements of state-owned companies on the Indonesia Stock Exchange were executive share ownership, CEO education and auditor changes. This study used a quantitative approach. The population in this study were 25 state-owned companies in the Indonesia Stock Exchange. The sampling technique used purposive sampling method with certain criteria in order to obtain a sample of 24 state-owned companies. The data in this study were analyzed using the help of IBM SPSS version 25 by testing multiple linear regression analysis. The results of this study indicated that share ownership partially affected the fraudulent financial statements of BUMN companies. Meanwhile, the results of CEO education and replacement of auditors partially had no effect on fraudulent financial statements of BUMN companies. As well as executive share ownership, CEO education and replacement of auditors simultaneously affected the fraud in the financial statements of BUMN companies.